Tumor-associated reactive astrocytes aid the evolution of immunosuppressive environment in glioblastoma - Heiland, Dieter Henrik; Ravi, Vidhya M.; Behringer, Simon P.; Frenking, Jan Hendrik; Wurm, Julian; Joseph, Kevin; Garrelfs, Nicklas W.C.; Strähle, Jakob; Heynckes, Sabrina; Grauvogel, Jürgen; Franco, Pamela; Mader, Irina; et al. (Nature Communications, 2019)
Reactive astrocytes evolve after brain injury, inflammatory and degenerative diseases, whereby they undergo transcriptomic re-programming. In malignant brain tumors, their function and crosstalk to other components of the environment is poorly understood. Here we report a distinct transcriptional phenotype of reactive astrocytes from glioblastoma linked to JAK/STAT pathway activation. Subsequently, we investigate the origin of astrocytic transformation by a microglia loss-of-function model in a human organotypic slice model with injected tumor cells. RNA-seq based gene expression analysis of astrocytes reveals a distinct astrocytic phenotype caused by the coexistence of microglia and astrocytes in the tumor environment, which leads to a large release of anti-inflammatory cytokines such as TGFβ, IL10 and G-CSF. Inhibition of the JAK/STAT pathway shifts the balance of pro- and anti-inflammatory cytokines towards a pro-inflammatory environment. The complex interaction of astrocytes and microglia cells promotes an immunosuppressive environment, suggesting that tumor-associated astrocytes contribute to anti-inflammatory responses.
CRIS-Team Scopus Importer:2023-09-13